Sistem Pengukuran Suhu Tubuh Menggunakan AMG8833 Dan Kinect Sebagai Pencegahan Penularan Covid-19 - Wiwin Lovita; Aulia; Junaldi (Ikatan Ahli Informatika Indonesia (IAII), 2022)
The purpose of this study is to create an effective and safe body temperature measurement system to prevent the transmission of covid-19 using the AMG8833 and Kinect. The method of sending data uses the Internet of Thing (IoT) and face tracking with 3D form as face identification using a kinect type xbox 360 using an arduino uno and a buzzer connected to the AMG8833. AMG8833 has an infrared detector which is arranged in an 8x8 array and reads body temperature non-contact by detecting infrared energy from the body. kinect recognizes facial features based on the distance of the kinect position coordinates on the face. AMG8833 and kinect as input, Arduino uno as AMG8833 data processing and buzzer gives a sound signal if the temperature is above 37.10 0C. Body temperature measurement data was carried out 3 times, namely at a distance of 5,10 and 15cm. Measurement data from this body temperature measuring instrument are compared with a thermogun average error value of 0.11% with a difference between the maximum and minimum average body temperatures of 0.04%. It is hoped that body temperature measurements can be as a precaution against the spread of covid-19.